Waspada's Mass Media Strategy for Surviving in The Digital Age - Isra Della Aulia; Muhammad Alfikri (PT Mattawang Mediatama Solution, 2022)
Rapid technological advancement brings civilization to the mass media industry. The presence of new media in the community has created communication dynamics in the transmission of information. Traditional media must be able to align with transformation and innovation. Despite the flood of digital media, daily alert's main product remains newspapers. The constructivism paradigm and descriptive qualitative research methods were used in this study. In-depth interviews, observation, and documentation were used to collect data in this study. According to the findings of this study, mass media alert has a strategy to keep the newspaper alive in the digital era, an innovation strategy, a human resource management strategy, and a recognition of obstacles and solutions in order to stay alive in the digital era.